Field tests on a grease trap effluent filter - Wong, N. H.; Law, P.L; Lai, S.H. (Springer Science, 2007)
This study investigates the field performance tests of a commercial grease trap effluent filter for removal of total suspended solids, and oil and grease discharged from the clear zone of full service restaurant grease traps. The grease trap effluent filters were installed on 1,000-gallon, 2,000-gallon and 5,400-gallon full service restaurant grease traps over a period of 8 weeks, and samples were taken at the inlets and outlets. On average, the effluent filters demonstrated to be capable of removing 41% to 57% of TSS, and 43% to 52% of O and G. Field test data also showed that the total amount of TSS removed by the grease trap effluent filter installed on 1,000 gallon, 2,000 gallon and 5,400 gallon grease traps were approximately 2,542 kg, 709 kg, and 2,319 kg, respectively; and the total amount of O and G removed over the same period were approximately 1,104 kg, 271 kg, and 897 kg, respectively